Konsep Manajemen dalam melestarikan Budaya Cina Benteng dalam siaran Star Radio 107,3 FM - Hendra Hendra; Tri Angraeni; VIVIN HANITHA; Toni Yoyo; Rini Novianti (NEAR: Jurnal Pengabdian kepada Masyarakat, 2023)
Currently, the existence of radio is not as lively as it was in the previous era during its heyday. However, this seems to be refuted by the fact that radio continues to evolve with the times. Each region also currently has a local radio channel and is an attractive platform for community learning, working together for a common goal. So that discussing culture becomes interesting if it is done on air. Fort Chinese culture is interesting to discuss, especially how to maintain this culture so that it is not timeless and management concepts are very important to carry out in this regard. Based on this, on air broadcasts and YouTube streaming were carried out using a participatory method with the theme Management Concept in Preserving Fortress Chinese Culture on Star Radio 107.3FM broadcast.From the results of the broadcast that has been carried out, it has positive feedback with the number of radio viewers who watch it, seen from the radio rating during the broadcast and there is effective communication between the hosts, speakers and viewers through interactive discussions during the event.